Adaptation Transformation of Religious Education in Islamic Schools: Learning Innovation in SMP IT Al-Fityah and MTs Al-Munawwarah - Baihaqi, Baihaqi; Thohir, Kholis (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to identify the elements of innovation in learning, discern differences and similarities, and identify the potential for innovation in learning Islamic Religious Education within two Islamic schools in Binjai City. The research methodology employed a qualitative approach. Data collection techniques included in-depth interviews, observations, and documentation. The data underwent descriptive analysis involving data reduction, presentation, and conclusion. The results revealed that innovation in Islamic Religious Education learning in both Islamic schools in Binjai City is demonstrated through curriculum enrichment, encompassing enrichment, remedial, and coaching programs. At SMP IT Al-Fityah, the array of learning methods has expanded beyond lectures to incorporate discussions, exercises, assignments, homework, and presentations. Learning materials span from manual to digital, including LKS to e-learning, and encompass settings from traditional classrooms to laboratories. The assessment of learning in both schools employs both testing and non-test methods. Despite differences in the class grouping system - where SMP IT Al-Fityah employs small groups and MTs Al-Munawwarah adopts a package system - the commonality lies in utilizing the National Curriculum as the foundation for enriching Islamic Religious Education learning.